In silico drug-like properties prediction and in vivo antifungal potentials of Citrullus lanatus seed oil against Candida albicans - Victor Onukwube Apeh (Elsevier, 2022)
Citrullus lanatus seed is an important but neglected seed rich in essential fatty acids. The study sought to investigate in silico and in vivo antifungal activity of some bioactive compounds of Citrullus lanatus (watermelon) seed oil (CLSO) on oral candidiasis induced by Candida albicans in immunosuppressed female albino rats and to predict the Absorption, Distribution, Metabolism and Excretion (ADME) properties of isolated natural compound. Docking studies was performed using standard procedure, standard microbiological and histopathological techniques was employed for study of in vivo antifungal activity of the oil; as well as renal function tests at days 7 and 14 post-infection treatments. Treated groups were compared with that of the control groups. In vitro studies showed varied zone of inhibitions at different concentrations. Ligand-protein interaction showed better binding activity between Palmitic acid and SAP-5 as well as CYP51 when compared with fluconazole (reference drug). Treatment with CLSO showed that there was a significant reduction in the kidney fungal burden (cfu/ml/g) of rats treated with CLSO after 14 days post-infection treatment, compared to group 2 (untreated control) rats. Histomorphology of group 2 showed multifocal aggregation and widespread distribution of fungal blastospores when compared with CLSO-treated groups, which had minimal fungal blastospores in the renal tissues. Thus, in silico and histological data agreed with the findings in microbiology. Furthermore, within the CLSO treated group, a significant increase in the serum concentrations of creatinine was observed, while no significant difference in blood urea values was recorded after day 14 post-infection study. Linoleic and palmitic acid could be considered as a potential antifungal drug candidate with palmitic acid playing a significant role.